2009
DOI: 10.1111/j.1467-7652.2009.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing of mannose 6‐phosphate reductase in the parasitic weed Orobanche aegyptiaca through the production of homologous dsRNA sequences in the host plant

Abstract: SummaryOrobanche spp. (broomrape) are parasitic plants which subsist on the roots of a wide range of hosts, including tomato, causing severe losses in yield quality and quantity. Large amounts of mannitol accumulate in this parasitic weed during development. Mannose 6-phosphate reductase (M6PR) is a key enzyme in mannitol biosynthesis, and it has been suggested that mannitol accumulation may be very important for Orobanche development.Therefore, the Orobanche M6PR gene is a potential target for efforts to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 58 publications
3
96
0
Order By: Relevance
“…Published results showed effective b-glucuronidase silencing in the parasite via RNAi in the host roots (Tomilov et al, 2008). Similar results have recently been reported for control of the root parasite Orobanche in transgenic tomato that expresses RNAi for the parasite mannose 6-phosphate reductase in the host (Aly et al, 2009).…”
Section: The Usefulness Of Rnai As a Cross-species Parasitic Plant Cosupporting
confidence: 72%
See 2 more Smart Citations
“…Published results showed effective b-glucuronidase silencing in the parasite via RNAi in the host roots (Tomilov et al, 2008). Similar results have recently been reported for control of the root parasite Orobanche in transgenic tomato that expresses RNAi for the parasite mannose 6-phosphate reductase in the host (Aly et al, 2009).…”
Section: The Usefulness Of Rnai As a Cross-species Parasitic Plant Cosupporting
confidence: 72%
“…To examine the function of KNOX1 genes in dodder parasitism, we generated tobacco transgenics expressing an RNAi construct targeting the 39 untranslated regions (UTRs) of two dodder KNOX1 genes that do not share significant sequence similarity with the host encoded orthologs (STM and KNAT1-3; see Supplemental Figures 6 and 7 online). We hypothesized that small RNAs generated from the host-derived transgene might cause downregulation of endogenous parasite transcripts, as has been suggested by experiments using the plant holoparasite Orobanche (Aly et al, 2009). However, in that study, the nature of the host parasite interactions was not described and no transgene specific siRNAs were found in the parasite.…”
Section: Cross-species Rnai Of the Dodder Stm Genementioning
confidence: 78%
See 1 more Smart Citation
“…Consistent with the increased expression of SHOOT MERISTEMLESS-like (STM) at the time of haustoria induction, the ability to make haustoria was attenuated in dodder grown on host transgenics expressing dodder STM RNA interference using a phloem-specific promoter (Alakonya et al, 2012). Similar transspecific silencing of parasite genes encoding key enzymes caused reduced viability of the root parasites Orobanche aegyptiaca and Triphysaria versicolor (Aly et al, 2009;Bandaranayake and Yoder, 2013). However, manipulation of the expression levels of none of these genes provides complete control of the parasite, suggesting that suitable target genes for cross-species RNA silencing that will confer complete parasitic weed control remain to be identified.…”
mentioning
confidence: 85%
“…Recently, some researchers have reported the application of RNAi technology to develop weed-resistant plant varieties. Aly et al (2009) have produced transgenic tomato plants bearing M6PR dsRNA-expression cassette. They found that the level of endogenous M6PR mRNA in the tubercles and underground shoots of Orobanche aegyptiaca grown on transgenic tomato plants was reduced by 60-80 % with a significant decrease in mannitol level and a significant increase in the percentage of dead O. aegyptiaca tubercles.…”
Section: Parasitic Weeds Resistancementioning
confidence: 99%